SOCIAL MEDIA AND MINORITY LANGUAGES IN EVERYDAY LIFE: A COMPARATIVE ANALYSIS OF TWO TWITTER CAMPAIGNS PROMOTING THE IRISH LANGUAGE - Ní Bhroin, Niamh; McMonagle, Sarah (AoIR Selected Papers of Internet Research, 2020)
The Irish language (‘Gaeilge’), although the first official language of the Republic of Ireland, is a minority language in public life. In recent years, social media campaigns have been organised to promote the use of Irish online. In this paper, we analyse two such campaigns (#EDL #Gaeilge; and #TrasnaNadTonnta) and explore how participation in them is connected to everyday practices of media use and meaning making, and how this in turn influences minority language promotion in social media. Drawing on sociolinguistics and media and communication studies, we address the following research question: How can everyday life and media use influence participation in Twitter campaigns that aim to promote the Irish language? We find that the success of each campaign was dependent on the participants identifying connections between the campaigns and their everyday lives. #TrasnaNadTonnta found particular salience among the Irish diaspora, for whom the language is a marker of a unique cultural identity. This Twitter campaign provided a platform for Irish-language users to connect with others across Europe, North America, Asia and Australia – places where the Irish language has not been traditionally spoken. Although the same platform was provided in #EDL2017 #Gaeilge, Irish-language Twitter users did not identify with this campaign to the same extent. We further surmise that the unique hashtag created for #TrasnaNadTonnta, reminiscent of a song sung in childhood, had particular semiotic appeal when compared with the more policy-oriented approach of #EDL2017.